Costa Rica : Competitiveness Diagnostic and Recommendations - World Bank (World Bank, 2012)
Costa Rica is a clear success story. The country enjoys the highest standard of living in Central America and one of the highest in Latin America and the Caribbean (LAC). Not surprisingly, poverty levels are among the lowest in LAC. Indeed in 2004, Costa Rica had the second lowest poverty headcount in LAC with just nine percent of households below the US$2 poverty line. This report is a contribution to those efforts. Based on multiple data sources, it assesses the main obstacles that affect private sector growth in Costa Rica and provides policy options and targeted interventions for improving the business environment and increasing competitiveness, with the goal of achieving sustained and broad-based growth. In this regard, the main focus of the report is on the long-term instead of on cyclical issues. This report outlines a program to address the critical bottlenecks that hamper Costa Rica in diverse fields including infrastructure, technological innovation and quality, human capital, red tape, and access to credit. The result is a rich and encompassing agenda. The rest of the report is structured in the following way. In section two, the report diagnoses the principal obstacles to export growth and of competitiveness in Costa Rica. The diagnostics reveal four areas most in need of reform: infrastructure, human capital and innovation, business regulation, and access to finance. Sections three to six cover each of these areas. Finally, the report closes with a section on conclusions and recommendations.